RE-POSITIONING LOVE AS A VALUABLE PART OF LIFE - Muhammad Irfan Syaebani; Untung Yuwono; Embun Kenyowati Ekosiwi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Love is under threat because it is no longer something precious. In a culture steeped in capitalism, love becomes a commodity. Love turns into an instrument or tool for the achievement of something else. Love is considered something that cannot be found in real life and only remains in fiction and literature. Alain Badiou's schema of mathematics as ontology demonstrates that it is still possible to put love back as part of life and that love has value. Badiou reveals that initially, love is related to the self and is not a tool or instrument for anything outside the self. Love gives value to the human appreciation of life concerning its existence.